Conhecimentos, atitudes e práticas sobre Doença de Chagas de profissionais de saúde e pessoas acometidas em um município do interior do estado da Bahia - Bezerril, Ana Cláudia Rezende (2024)
Chagas disease (CD), in its chronic form, is a serious health problem in several areas of Brazil, including the state of Bahia. Despite being responsible for the illness and death of many people, it remains a neglected tropical disease (NTD). Identifying those affected or at risk should be a priority in endemic areas, as should establishing consistent processes for comprehensive treatment and care. However, there are numerous challenges, including weaknesses in training and health education processes, which can affect the attitudes and practices of professionals, managers and affected individuals. The aim of this study was to analyse the knowledge, attitudes and practices of people affected by CD and health professionals from endemic areas in the interior of Bahia. This was a cross-sectional study carried out in the municipality of Vitória da Conquista - south-west Bahia, between 2023 and 2024. The sample consisted of 501 health professionals from primary health care (PHC) and entomological surveillance in the municipality, 39 nurses and 31 doctors; 337 community health workers (CHWs) and 94 endemic disease control workers (EDCWs); and 36 people affected by CD. Simple and relative frequencies were analysed using Stata 11.0 software. It was found that a minority of doctors and nurses (n=3;4.2%) recognised having a family member diagnosed with CD as a risk condition, and for the majority (n=31;43.7%). It is worth noting the low percentage of people with or suspected of having CD in PHC (n=7;9.9%), with little practice in prescribing aetiological treatment (n=15;21.1%). Among CHWs and EDCWs only a minority (n=59;13.8%) know someone with CD; the majority do not know how to make a diagnosis (n=234;54.9%) and many (n=233;54.7%) say they do not know how to advise a person with CD. A significant percentage (n=245; 57.5%) believe that they are unable to suspect a case of CD based on the user's complaints. The non-use of information/educational material on CD in programme actions at the health unit (n=337; 79.1%) and in the area (n=375; 88.0%) is quite common. From the point of view of people with CD, a significant percentage (n=25;69.4%) say they don't know how CD is diagnosed and where the tests are carried out (n=27;75%). There was a higher proportion of people with CD who did not receive any follow-up care (n=13;36.1%). The majority do not take care of their health in relation to CD (n=17; 47.2%). When asked directly about annual follow-up appointments, 61.1% (n=22) reported not having any. The study reveals limited knowledge of aspects related to monitoring, diagnosis and treatment of CD. This condition influences the adoption of incorrect attitudes and practices regarding CD surveillance and care. It therefore reinforces the need for PHC to adopt permanent educational and community health education measures capable of promoting changes in professional and community practices. The incorporation of strategies adapted to the socio-cultural context and the specific profile of professionals and users can be crucial for effective control of the disease in endemic areas. This is an essential condition for overcoming contexts of acknowledged neglect.